Studi Pengaruh Jenis Refrigerant Terhadap Pemakaian Daya Listrik Pada Mesin Pengkondisian Udara (AC) - Mudana, I Nyoman; Sudarmojo, Yanu Prapto; Janardana, I Gusti Ngurah (Jurnal SPEKTRUM, 2018)
Air conditioning is strongly influenced by Refrigerant. R.22 refrigerant is currently still widely used with high level of electric power consumption. The purpose of this research is to analyze the influence of types of refrigerant to the electric power consumption of AC by measuring the electric power requirement of each Refrigerant (R.22, R.410, R.32, EnggasM60 and Isceon MO99). The results showed that R.410 uses 335 Watt with the total cost of Rp 42,210 / month, R.32 uses 328 Watt power with the total cost of Rp 41.328 / month, R.22 uses 271 Watt power with theotal cost of Rp 34.146 / month, Huffin M60 uses 262 Watt power with the total cost of Rp 33.012 / month. While Isceon M099 requires 262 Watt with the total cost of Rp 33.012 / month at the temperature of 24,4 ° C.